Analisis Pertumbuhan Pro Poor di Pulau Sumatera Periode 2013-2023 - Setiawan, Syarif; Rahmizal, Maizul; Amar, Syamsul (Universitas Negeri Padang, 2025)
The aim of this research is to initiate pro-poor improvements on the island of Sumatra. Fixed Effects Model, also known as FEM is used to analyze panel data along with PPGI. This research involves two dependent variables: income distribution inequality and poverty, as well as two independent variables GRDP per capita and income distribution inequality. The results show that GRDP per capita has a significant negative effect on the Inequality of Income Distribution on the Island of Sumatra, GRDP per capita has a significant negative effect on Poverty on the Island of Sumatra, Inequality of Income Distribution has a significant positive effect on poverty and strong pro-poor growth on the Island of Sumatra.